Physical activity and mammographic density in an Asian multi-ethnic cohort - Soh, Wee Heng; Rajaram, Nadia; Mariapun, Shivaani; Eriksson, Mikael; Fadzli, Farhana; Ho, Weang Kee; Mohd Taib, Nur Aishah; Hall, Per; Teo, Soo Hwang (Springer, 2018)
Background: Physical activity is a modifiable lifestyle factor associated with reduced breast cancer risk. Mammographic density is a strong, independent risk factor for breast cancer, and some breast cancer risk factors have been shown to modify mammographic density. However, the effect of physical activity on mammographic density, studied predominantly among Caucasians, has yielded conflicting results. In this study, we examined, in an Asian population, the association between physical activity and mammographic density. Methods: We conducted a cross-sectional study of 2,377 Malaysian women aged 40–74 years. Physical activity information was obtained at screening mammogram and mammographic density was measured from mammograms by the area-based STRATUS method (n = 1,522) and the volumetric Volpara™ (n = 1,200) method. Linear regression analyses were performed to evaluate the association between physical activity and mammographic density, adjusting for potential confounders. Results: We observed that recent physical activity was associated with area-based mammographic density measures among postmenopausal women, but not premenopausal women. In the fully adjusted model, postmenopausal women with the highest level of recent physical activity had 8.0 cm2 [95% confidence interval: 1.3, 14.3 cm2] lower non-dense area and 3.1% [0.1, 6.3%] higher area-based percent density, compared to women with the lowest level of recent physical activity. Physical activity was not associated to volumetric mammographic density. Conclusions: Our findings suggest that the beneficial effects of physical activity on breast cancer risk may not be measurable through mammographic density. Future research is needed to identify appropriate biomarkers to assess the effect of physical activity on breast cancer risk.